Pengaruh Literasi Keuangan, Teknologi Keuangan, dan Kompetensi Manajerial Terhadap Pengelolaan Keuangan UMKM di Kabupaten Seleman Yogyakarta - Karo, Cindy Theresia Br; Styani, Astuti Yuli (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of financial literacy, financial technology, and managerial competence on the financial management of MSMEs in Sleman Regency, Yogyakarta. This research employs a quantitative approach using a survey method, with questionnaires distributed to 126 MSME respondents. Data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that financial literacy has no significant effect on MSME financial management. In contrast, financial technology and managerial competence have a positive and significant influence. Simultaneously, all three variables significantly affect financial management. The coefficient of determination (R²) of 0.113 implies that the independent variables explain 11.3% of the variation in financial management, while the remaining 88.7% is influenced by other factors beyond this study. These findings highlight the importance of technology utilization and managerial capability in improving MSME financial governance.